Augmented Reality Appling with Consistency of Behavior using Oriented Bounding Box Algorithm - et. al., Abdul-Wahab Sami Ibrahim, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Augmented reality can be defined as the process of merging digital information in real videos, it plays big role in many application such as education, medicine, and media industries. The merging of virtual moving object into real videos consists of two main stages: the detection of moving objects into real videos and the collision detection between real and virtual objects. In this study, an algorithm for merging virtual moving object into real video has been proposed, it is based on the three frame differencing technique followed by two pre-processing steps to detect real moving object. While the collision detection stage is based on the intersection between moving object path and the bounding box of real object. The experiment results show the good accuracy of the proposed algorithm in extracting moving object and merging virtual object into video frames.